Scheduled castes - "Kamble, N. D." (New Delhi, 1982)
Indian society was historically divided into four graded varnas of Brahmins, Kshatriyas, Vaishyas and Sudras. There were only first three varnas, but the fight between Brahmins and Kshatriyas for the supremacy gave birth to the fourth varna of Sudras. Sudras were the defeated Kshatriyas who oppressed with the help of social and economic and cultu ral laws. Most of the laws were detrimen tal to the interests of Sudras. The regressive laws did not give any chance to Sudras to rise their head in later period. Those people who did not accept or practice the law of varna system were further degraded and were known as Avernas Panchamas. or Those castes among Avernas, due to whose touch, ritual purity was believed to disapp ear were treated as untouchables. Nations of ritual purity and pollution were introdu ced to justify the suppression of Avernas and support the regressive laws which were made to keep the system intact. Bulk of the untoucables were once Buddhists. Conflict between Buddhists and vedic religion for supremacy lead to the destruction of Buddh ism and degradation of Buddhists. They were deprived of the right of the property, educa tion, equality and opportunities during their life time. They were assigned low status even when they were in the womb and could not be changed even after they are in tomb The then Buddhists were much afraid of disclosing themselves as Buddhists due to the fear of oppression/ After the eleventh century, Muslim fanatic invaders, destroyed Buddhist shrines and butchered many Buddhists as they could be easily identified because of their ropes. Untouchables were serfs and slaves who could be purchased, sold and mortgaged like commodities. Lately British Government in India banned the slave trade in 1792 and gave some protec tion to them in 1862. However, British Government was not interested in protecting them because of the fear of dominant local high castes. These castes were systemati cally listed in 1936 in a schedule and were referred to as SC in 1936 by Government of India order.
Keywords: Castes